Cover. Issue 10 (17th October 2022) - Green, Ariel R.; Aschmann, Hélène; Boyd, Cynthia M.; Schoenborn, Nancy
Abstract : Cover captions : Health outcome priorities related to deprescribing. See the related article by Green et al., pages 2895–2904 .